Pengembangan Aplikasi Rekomendasi Musik Berdasarkan Cuaca Pada Platform Android - Ahmad Wildan Rizaldy; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Music is one of the biggest human entertainment. With digital music and the internet, there is so much music that can be listened to by the million users. Music recommendation is the recommendation system that exists not only because there is so much music out there, but because the perception about music is still cannot be fully understood. At the moment, there is a need for a recommendation system that suits the requested context. The Music Recommendation System based on Weather help user to find their music that fits with the context they are in. The development of this system is to make an android application and using an expert system method with forward chaining. this system will process input that the user input and the output will be a recommendation of music that fits the expert rule. Functional testing of this system resulting in a valid outcome which means this system grade is 100%. While usability testing of this system outcome is 76.5 in value of system usability scale which means it's acceptable. Then the accuracy testing that will compare the output system and the expert, the system comes out with 100% accuracy.